Manajemen Coaching dan Mentoring dalam Pengelolaan Aksi Perubahan Peserta Pelatihan Kepemimpinan Administrator - Hidayat, Taufik (CV. Creative Tugu Pena, 2022)
The purpose of this study was to determine 1) the implementation of coaching and mentoring in the implementation of PKA change management in Lampung Province; 2) the factors influence the management of coaching and mentoring in the implementation of Administrator Leadership Training in Lampung Province; and 3) the form of follow-up that would be carried out as an effort to improve the management of coaching and mentoring in the management of Pelatihan Kepemimpinan Administrator (PKA). This study used a qualitative descriptive approach. The data in this study were obtained through questionnaires submitted to participants, mentors, and coaches with a total of 77 people. The data analysis procedure used an interactive model, namely data collection, data reduction, data presentation; and Drawing conclusions and Verification. The result found that most of the Change Actions experienced obstacles in post-training implementation. To achieve optimal training results, it was necessary to improve the coaching and mentoring mechanism. Improvements that need to be carried out by activities that include appointing coaches must consider competencies as evidenced by coaching certification, coaching is carried out in building participant commitment and including Changes Action achievements in Employee Performance Targets (SKP), Determination of direct supervisors of training participants with assignments as mentors accompanied by a written commitment statement , and conduct pre-training that would be support the success of the training. Keywords: Manajemen Coaching Mentoring, Participant Action Management, Administrator Leadership Training